Azo dye degradation by bacterial laccases produced from mushroom spent - shah, Yash; Padma, P. Naga; Anuradha, K. (International Journal of Scientific Research in Biological Sciences, 2019)
Laccases are multi-copper enzymes which catalyze the oxidation of a wide range of phenolic and non-phenolic aromatic compounds and participate in several applications such as bioremediation, biopulping, textile, and food industries. It is widely distributed in higher plants, fungi and also found in bacteria. Azo dyes containing effluents from different industries pose threats to the environment. Though there are physico-chemical methods to treat such effluents, bioremediation is considered to be the best eco-friendly method. The present study emphasises on isolation of efficient laccase producers from mushroom spent and their use for azo dye degradation. The primary isolates were isolated by enrichment culture technique using guaiacol as substrate. About 10 secondary isolates were studied for laccase production using raw substrate like saw dust. The isolates were identified culturally, microscopically and biochemically. The laccase production cycle for the isolates was studied and found that peak production was by 72 hours. The selected laccase producers were tested for their different azo dye degradation potential both in isolation and as a consortium. The different azo dyes studied were trypan blue, congo red, malachite green and methyl red dyes for degradation at regular intervals of 24 hours for a period of 3 days. The different concentrations studied were 10mg/L, 25mg/L, 50mg/L, 75mg/L, 100mg/L. The consortium of Azo dye degrading cultures (samples 1–5) could totally degrade all azo dyes with variation in degradation times, whereas isolates could only degrade methyl red with variation in time. The samples 2 and 5 showed complete degradation of methyl red in 48 hours and other applications can be further studied.